South Tower on Treasure Island and Court of the Moon (H.S. Crocker Co., Inc.)
The Tower on the Mines, Metals, and Machinery Building, one of the two great South Towers of the San Francisco World's Fair, looks down upon Treasure Garden and the beautiful Court of the Moon.